Rural development and rural tourism in the municipality of Petrovac na Mlavi - Babić, Vedrana; Lala Davidov, Radovan; Jovanović, Marko (Economics of Agriculture, 2018)
Community Petrovac na Mlavi is located in Eastern Serbia, in county Branicevo. His spread 654. 9 km². By the census in this community lives 45 706 inhabitants (Serbian and Vlahian origin). City Petrovac as the center of community has 8 772 inhabitant Relief is represented with hills and plains. Climate is moderate continental. Hidrography is represented by river Mlava with her fributeries. Tis community is tich with different animal and herbal species. Economy of community is undeveloped, but natural and antropogenik fortune, peace, silence, green nature, loveliness of housekeeper… are important potential for development of rural tourism. Plan of community Petrovac is to give a special attention for development of rural tourism and activation of country’ s housing and inhabitation on this community. The theme of paper is a connection between rural (sustainable ) development and rural tourism like possibility of development in community Petrovac. Rural tourism throughout the country, especially in economically disadvantaged and less developed areas, such as municipalities Petrovac na Mlavi, can have multiple positive effects not only on individual rural households, but also the overall development of rural space. The cause is to show a possibility of development a rural tourism on this area. Authors of this work is date collection trough experience on tarain, area monitoring and benchmarking.